MODEL PEMBELAJARAN CRI DENGAN TEKNIK IOC: PENGARUHNYA TERHADAP KEMAMPUAN PEMECAHAN MASALAH DAN KEMAMPUAN KOMUNIKASI MATEMATIS - Anita Rahayu Pamintaningsih; Ruhban Masykur; Suherman Suherman (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
The ability to solve problems and the ability to communicate mathematically in a student's study is a skill that students need to provide asa basis for resolving mathematical problems. Based on the results of daily mathematicians saying that the ability to solve problems and mathematical communications at MTS Darul A'mal Metro is still low, judging by the student's process of resolving mathematical problems caused by many who pay no attention to the explanations presented by teachers and students are not able to solve math problems properly. In addition, there are less diverse learning models. To address the problem, researchers applied the CRI model with IOC techniques. The purpose of this study is to know the difference between the CRI learning model with the IOC and the direct learning model of problem solving and student mathematical corover. This research is an experiment quasy research. Sample demonstration techniques using the simple random sampling technique. The samples in this study are class VII D as an experiment class and class VII E as a control class. The instrument used to collect data is a description test. The custom data analysis technique used was the normality test, the homogenity test and the hypothetical test used the manova test. Based on manova's test results of Pillai's Trace, Wilks' Iambda, Hotelling's Trace, Roy's Lagest Root  and value a test criteria  which means that the p-value value is smaller than a test criteria, so that ho is thus denied it can be inconclusive that there is an influence between the CRI model and the IOC techniques of student solving and mathematical communication capability